Relationship between stock auditory memory and reading comprehension, in students of fifth and sixth in Lima primary and Huarochirí - Yaringaño L., Juan (2009)
This study explores the relationship between reading comprehension and auditive memory immediate groups of students in primary education of Huarochirí and Lima. The subjects were selected according to the probabilistic approach not intentional, comprising 228 students from state schools of the district of San Juan de Lurigancho and San Mateo, fifth and sixth grade and both sexes, which were evaluated with the Test Auditive Memory Immediate and the Test of Linguistic Complexity Progressive, with the aim of knowing the levels of auditive memory immediate and reading comprehension. The implementation of the instruments was conducted in a collective manner. The descriptive analysis of the data was done through the distribution of frequencies and measures of central tendency, for analysis and inferential statistical tests were used U Mann-Whitney and Spearman Rho. The results showed a correlation modest (Rho=0,430) between reading comprehension and auditive memory immediately. The comparative statistical analysis indicated significant differences in auditive memory instantly by where they live and degree studies, as well as in reading comprehension depending on the degree of study. By contrast not be found significant differences in auditive memory immediate and reading comprehension by gender.